Comparison of High-Throughput Fully Automated Immunoanalyzers for Detecting Hepatitis B Virus Infection - Won, Dongju; Park, Younhee; Choi, Dasom; Kim, Hyon-Suk (Archives of pathology & laboratory medicine (1976), 2020)
High-throughput automated immunoanalyzers for hepatitis B virus serologic markers have been introduced but have not been compared to existing systems. To compare hepatitis B surface antigen, hepatitis B surface antibody, and total hepatitis B core antibody analyses between our Architect i2000 platform and newer high-throughput fully automated immunoanalyzers. From May to June 2018, a total of 932, 914, and 1055 samples tested for hepatitis B surface antigen, hepatitis B surface antibody, and total hepatitis B core antibody, respectively, with the Architect i2000 system for routine testing in our center were tested again with Alinity i, Atellica IM, and Cobas e801 systems. Total concordance rates among the systems were 98.0%, 89.5%, and 93.0% for hepatitis B surface antigen, hepatitis B surface antibody, and total hepatitis B core antibody, respectively. Cohen's κ values exceeded 0.8. The correlations between serum hepatitis B surface antibody levels quantified by all 4 systems were high ( > 0.85). The hepatitis B surface antibody averages were greater for the Alinity i, Atellica IM, and Cobas e801 than for the Architect i2000 ( < .001). Alinity i, Atellica IM, and Cobas e801 automated immunoanalyzers performed well when compared with the existing Architect i2000 system with regard to detection of hepatitis B viral infection. However, the new systems have higher titer and positivity rates for hepatitis B surface antibody and are more sensitive. Notably, the Atellica IM has a lower positive rate for total hepatitis B core antibody than does the Architect i2000.